Edukasi Sistem Sanitasi dan Drainase Rumah Tangga di Desa Ngaresrejo Sidoarjo - Yayu Sriwahyuni Hamzah; Sebastianus Priambodo; Muhammad Saul Bayustira (Fakultas Teknik Universitas Palangka Raya, 2026)
Sanitation and drainage problems at the household level continue to pose challenges in residential environments, largely driven by inadequate understanding of proper domestic waste handling. This community engagement initiative was designed to improve public knowledge and raise awareness of effective and sustainable sanitation and drainage practices. The activity was conducted in Ngaresrejo Village, Sidoarjo Regency, involving approximately 25 participants through a participatory approach. The methods applied included preliminary surveys, interactive educational sessions, audio-visual demonstrations, and evaluation using pre-test and post-test instruments. The results indicated a substantial improvement in participants’ understanding, increasing from approximately 21,2% at the initial stage to 88,8% after the intervention, representing an improvement of about 67,6%. In addition, participant attendance and engagement were high, and most participants expressed willingness to implement improved sanitation practices at the household level. All program success indicators were achieved, including increased awareness and the development of educational materials. Accordingly, the initiative proves effective in strengthening public understanding and shows promise in supporting long-term improvements in environmental conditions within residential settings.